KOMBINASI ALGORITMA KRIPTOGRAFI RC6 DAN STEGANOGRAFI LSB UNTUK PENGAMANAN PESAN TEKS - Ferawati Kai; Agusyarif Rezka Nuha; Asriadi Asriadi; Hasan S. Panigoro; Nisky Imansyah Yahya; Armayani Arsal (MATHunesa: Jurnal Ilmiah Matematika, 2025)
The rapid advancement of technology has led to various types of technological crimes. One solution to secure messages is by using cryptographic and steganographic techniques. This research combined the Rivest Code 6 (RC6) cryptographic algorithm and the Least Significant Bit (LSB) steganographic algorithm to enhance message security. The study analyzed changes in an image embedded with a message and sent through applications such a WhatsApp, Telegram, and E-mail. The final result show that the image embedded with the message does not undergo significant changes. However, stego images sent directly via WhatsApp and Telegram experience size alterations, which cause the embedded messages to become corrupted. Meanwhile, stego images sent as documents retain their size, allowing the message to remain intact. Additionally, stego images sent via E-mail, either as attachments or directly, do not experience size changes, and the embedded messages can be fully retrieved.